A Sharia-Based Strategic Human Resource Management Model for the National Amil Zakat Agency (BAZNAS) - Moch Aminudin Hadi; Cahyo Budi Santoso; Netty Syafitri; Robby Kurniawan; Yuddy Giovanna Priscilla (Annals of Human Resource Management Research, 2026)
Purpose: This study aims to formulate a comprehensive Sharia-based Strategic Human Resource Management (SHRM) model for the National Amil Zakat Agency (BAZNAS). The model integrates spiritual, moral, and professional values to enhance the organization’s effectiveness and accountability in managing zakat institutions. Research Methodology: A qualitative research approach with an interpretive phenomenological design was employed. Data were collected through in-depth interviews, participatory observations, and document analysis involving eight purposively selected key informants. Data validation was ensured through triangulation and member checking. Results: The findings show that SHRM at BAZNAS is shaped by three key dimensions: foundational (zakat fiqh), external (regulation, digitalization, and global factors), and internal (leadership and organizational culture). Twelve core values integrate spiritual, moral, and professional aspects, whereas HRM functions focus on planning, retention, and development within a Sharia framework. Conclusions: A distinctive Sharia-compliant SHRM model is crucial for strengthening professionalism, accountability, and public trust, thereby enabling zakat institutions to enhance their socioeconomic roles. Limitations: This study is limited by its qualitative design, small sample size, and Indonesian context, which may affect its generalizability. Contributions: This study offers a novel integration of Sharia principles into strategic HRM for non-profit institutions, contributing theoretically to Islamic HRM literature and practically to HR policy and strategic planning in zakat organizations.